Fucoidan Promotes the Reconstruction of Skin Equivalents - Song, Yu Seok; Li, Hailan; Balcos, Marie Carmel; Yun, Hye-Young; Baek, Kwang Jin; Kwon, Nyoun Soo; Choi, Hye-Ryung; Park, Kyoung-Chan; Kim, Dong-Seok (The Korean journal of physiology & pharmacology, 2014)
In this study we investigated the effects of fucoidan on the proliferation of fibroblasts and the reconstruction of a skin equivalent (SE). Fucoidan significantly stimulated the proliferation of CCD-25Sk human fibroblasts and Western blot analysis demonstrated that fucoidan markedly increased the expression of cyclin D1 and decreased the expression of p27. Fucoidan was used to reconstruct SE. Immunohistochemical staining showed that the addition of fucoidan to dermal equivalents increased expression of proliferating cell nuclear antigen (PCNA) and p63. In addition, expression of α6-integrin was significantly increased by fucoidan, whereas expression of β1-integrin, type 1 collagen, elastin, fibronectin did not markedly change. These results suggest that fucoidan has positive effects on epidermal reconstruction and will therefore be beneficial in the reconstruction of SE.